Development Of The Smarty-Ai Model Within The Understanding By Design Framework To Enhance Students Critical Thinking Skills - Nurlinda Safitri; Indri Yani; Ratih Purnamasari; Hanifah Tri Nur Fadillah (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2026)
This study aims to develop and examine the effectiveness of the SMARTY-AI Model within the Understanding by Design (UbD) framework integrated with Artificial Intelligence (AI) in improving elementary school students critical thinking skills. The research employed a Research and Development (R&D) method consisting of model development stages, expert validation, and effectiveness testing through a quasi-experimental design involving experimental and control groups. The findings revealed that the SMARTY-AI Model achieved a very high level of feasibility based on expert validation results, with an average score of 92.6%. Furthermore, the effectiveness test indicated a more significant improvement in learning outcomes in the experimental class compared to the control class. The N-Gain score in the experimental class was 0.61 (moderate category), while the control class obtained 0.29 (low category).These findings indicate that the integration of the Understanding by Design approach with Artificial Intelligence support in the SMARTY-AI Model is effective in enhancing elementary school students’ critical thinking skills. This model can serve as an innovative alternative for 21st century learning that emphasizes the development of higher-order thinking skills.